ORGANIZATIONAL DESIGN, INTERNAL COLLABORATION AND PERFORMANCE: AN EMPIRICAL ASSESSMENT IN LATVIA - Ludviga, Iveta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
We live in the time of transformations and in response to environmental challenges, traditional forms of organizational designs are changing towards more networked ones. Human resource practitioners claim that ‘Organization of the future’ requires freedom to act, flexible working practices, outcome-based performance management, and high-trust working relationships, however, there is limited empirical attention directed to the elements of organizational structures, and organizational design aspects have not been explicitly addressed. This research aims to identify which organizational design mechanisms facilitate collaboration within organizations and positively contribute to organizational performance. The quantitative study uses data from a structured survey of Latvian organizations.  The research findings provide empirical evidence of the positive impact of decentralization, outcome-based performance management and internal trust on collaboration within the organizational boundaries and performance measured as customer satisfaction. Assessing differences between organisations it was found that internal trust appears to be even more important collaboration ensuring factor for large organizations than for smaller ones.  Research results show that managers should establish internal trust-based relationships within their organizations since the effect of trust on collaboration could not be overestimated.